Long-Term Motor Recovery After Severe Traumatic Brain Injury: Beyond Established Limits. Issue 5 (September 2016) - D'Arcy, Ryan C. N.; Lindsay, D. Stephen; Song, Xiaowei; Gawryluk, Jodie R.; Greene, Debbie; Mayo, Chantel; Ghosh Hajra, Sujoy; Mandziuk, Lila; Mathieson, John; Greene, Trevor
Abstract : Objective: To report neural plasticity changes after severe traumatic brain injury. Setting: Case-control study. Participants: Canadian soldier, Captain Trevor Greene survived a severe open-traumatic brain injury during a 2006 combat tour in Afghanistan. Design: Longitudinal follow-up for more than 6 years. Main Measures: Twelve longitudinal functional magnetic imaging (fMRI) examinations were conducted to investigate lower limb activation changes in association with clinical examination. Trevor Greene's lower limb fMRI activation was compared with control fMRI activation of (1) mental imagery of similar movement and (2) matched control subject data. Results: Trevor Greene's motor recovery and corresponding fMRI activation increased significantly over time ( F = 32.54, P < .001). Clinical measures of functional recovery correlated strongly with fMRI motor activation changes ( r = 0.81, P = .001). By comparison, while Trevor Greene's mental imagery activated similar motor regions, there was no evidence of fMRI activation change over time. While comparable, control motor activation did not change over time and there was no significant mental imagery activation. Conclusion: Motor function recovery can occur beyond 6 years after severe traumatic brain injury, both in neural plasticity and clinical outcome. This demonstrates that continued benefits in physical function due to rehabilitative efforts can be achieved for many years following injury. The finding challenges current practices and assumptions in rehabilitation following traumatic brain injury.